Clinical Activity of Pazopanib in Patients with Advanced Desmoplastic Small Round Cell Tumor. (6th December 2017) - Menegaz, Brian A.; Cuglievan, Branko; Benson, Jalen; Camacho, Pamela; Lamhamedi‐Cherradi, Salah‐Eddine; Leung, Cheuk Hong; Warneke, Carla L.; Huh, Winston; Subbiah, Vivek; Benjamin, Robert S.; Patel, Shreyaskumar; Daw, Najat; et al.
Abstract : Background: Desmoplastic small round cell tumor (DSRCT) is an aggressive, often fatal soft tissue sarcoma that lacks an optimal salvage regimen. We retrospectively reviewed data from 29 pretreated DSRCT patients who received pazopanib at MD Anderson Cancer Center after failure of standard chemotherapies. Subjects, Materials, and Methods : Medical records of patients treated from January 2012 to December 2016 were reviewed and regression analyses were performed. Median progression‐free survival (PFS) and overall survival (OS) were estimated using the Kaplan‐Meier method and differences in survival were assessed by a log‐rank test. A landmark statistical analysis was used to assess OS at a predefined 12‐week time point following pazopanib initiation. Results : The mean age at pazopanib treatment was 27.5 years (range, 6.3–50.1 years). According to RECIST 1.1 criteria, 16 patients (55%) had stable disease, 1 patient (3%) had partial response, 1 patient (3%) had complete response, and 11 patients (38%) had progressive disease. Estimated median PFS was 5.63 months (95% confidence interval [CI]: 3.23–7.47). Median OS was 15.7 months (95% CI: 10.3–32.4). As of December 2016, 11 patients (38%) were still alive, with a median follow‐up time of 16.8 (range 3.8–30.1) months. Doses between 400 and 800 mg were included. Pazopanib was well tolerated and 23 (79%) of the patients continued it until progression or death, 4 discontinued because of side effects, and 2 were still on pazopanib at the time of data analysis. Conclusion : In the largest study conducted to date in DSRCT, pazopanib was well tolerated and clinically active in heavily pretreated patients who otherwise lack good treatment options. Implications for Practice: Desmoplastic small round cell tumor (DSRCT) is a rare, extremely aggressive soft tissue sarcoma subtype that most commonly occurs in adolescent and young adult males. No DSRCT‐specific therapies exist, and for lack of a better treatment approach, current therapies have relied upon U.S. Food and Drug Administration‐approved drugs like pazopanib that exhibit clinical activity in other sarcoma subtypes. This article describes the largest experience to date using pazopanib as salvage treatment in heavily pretreated DSRCT patients. Pazopanib was well tolerated and clinically active, surpassing predefined metrics proposed by the European Organization for Research and Treatment of Cancer indicative of "active" sarcoma drugs (5.63 months progression‐free survival [PSF], with 62% of the study population achieving progression‐free survival at 12 weeks). Abstract : Desmoplastic small round cell tumor (DSRCT) is an aggressive, usually incurable, soft tissue sarcoma subtype that presents with diffuse abdominal sarcomatosis in adolescents and young adults. This article presents the largest retrospective analysis conducted to date of patients with DSRCT who were treated with an anti‐angiogenic therapy.